2019
DOI: 10.1109/access.2019.2913685
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Pattern Classification for Automatic Dementia Detection

Abstract: This paper proposes a novel technique for the automatic detection of dementia based on the attentional matrices test (AMT) for selective attention assessment. The original test provides three matrices, of increasing difficulty, and the test taker is asked to mark target digits assigned. In our proposal, AMT was developed on a digitizing tablet, equipped with an electronic pen. Tablet technology enables the acquisition of additional measures to those that can be obtained by observing the execution of the tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…The Attentional Matrice test, instead, is a cancellation test in which the subject is asked to mark target digits assigned among several distractors. In Reference [42], it was shown how the perceptual decision while scanning, easily captured by in-air movement analysis, is impaired in cognitively deteriorated subjects.…”
Section: Complex Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…The Attentional Matrice test, instead, is a cancellation test in which the subject is asked to mark target digits assigned among several distractors. In Reference [42], it was shown how the perceptual decision while scanning, easily captured by in-air movement analysis, is impaired in cognitively deteriorated subjects.…”
Section: Complex Tasksmentioning
confidence: 99%
“…In Reference [42], Angelillo et al proposed a digitized version of the Attentional Matrices Test for selective attention assessment: it is based on three matrices of increasing difficulty, and the subject is asked to the mark target digits assigned. The authors observed how, although a pathological matrix may look "normal" if considering only the on-surface pattern, the information provided by in-air movements reveal a completely deteriorated search strategy of the targets to be marked among the distractors.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…Novel insights could be obtained, for example, by using a multi-expert approach or a set of fuzzy inference rules. Promising results from using these techniques for diagnostic purposes in other domains have been recently reported, e.g., [52,53]. A multi-expert approach, which is based on ensembling different classifiers trained for the same task, may further improve prediction accuracy, as it can benefit from the different viewpoints from which these classifiers may look at the data.…”
Section: Discussionmentioning
confidence: 99%
“…Novel features like sensor (digital) data, handwriting (text), and speech (audio), offer unique opportunities to identify new indicators of cognitive decline (Kourtis et al, 2019). The five exemplar studies in Table 1 include home-based motion sensors (Akl et al, 2015), computerized handwriting analyzes (Angelillo et al, 2019), videotaped handwashing tasks (Ashraf and Taati, 2016), multi-modal wearable activity monitors (Gwak et al, 2018), and audio-recorded speech data (Toth et al, 2018) for detecting cognitive impairment. These data (particularly environmental and wearable sensors) have the potential for continuous, longitudinal tracking of cognitive changes.…”
Section: Novel Assessments (Sensors Handwriting Speech) (Table 1 Sementioning
confidence: 99%